Respuesta :
2r^2 + 3s^3 - r^2 + 4t^2 - r^2
r = -2
s = -3
t = 5
First we should substitute everything into the expression
(2)((-2)^2) + (3)((-3)^3) - (-2^2) + (4)(5^2) - (-2^2)
Now we should simplify the exponents
(2)(4) + (3)(-27) - (4) + (4)(25) - (4)
Now we simplify the brackets
8 + (-81) - 4 + 100 - 4
so 8 minus 81 minus 4 plus 100 minus 4 is equal to +19
r = -2
s = -3
t = 5
First we should substitute everything into the expression
(2)((-2)^2) + (3)((-3)^3) - (-2^2) + (4)(5^2) - (-2^2)
Now we should simplify the exponents
(2)(4) + (3)(-27) - (4) + (4)(25) - (4)
Now we simplify the brackets
8 + (-81) - 4 + 100 - 4
so 8 minus 81 minus 4 plus 100 minus 4 is equal to +19